Spectrogram Analysis of Complete Dentures with Different Thickness and Palatal Rugae Materials on Speech Production - Hamada Zaki Mahross; Kusai Baroudi (Hindawi Limited, 2015)
Objective. To investigate the influence of reproduction of different thickness and palatal rugae materials on complete dentures speech using Computerized Speech Lab (CSL) (spectrogram). Materials and Methods. Three completely edentulous male patients (aged 50-60 years) were selected for reading a paragraph. Twelve upper dentures were constructed, four for each patient. The patients' speech groups were divided into five groups, Group I: patients without dentures; Group II: patients rehabilitated with conventional acrylic dentures; Group III: patients with conventional acrylic dentures with rugae reproduction; Group IV: patients with dentures with metallic framework of minimal thickness and direct ragged metallic palatal surface at rugae area; Group V: patients with dentures with palatal rugae constructed from resilient acrylic resin material with thickness less than conventional denture. Speech samples were recorded after insertion of each denture for groups using Computerized Speech Lab (CSL) (spectrogram). The sounds selected were lingopalatal /s/z/sh/t/d/ and /l/. Results. Group III produced high mean significant difference with /sh/t/ sound. For Group IV, the difference was noticed with /s/z/sh/t/ and /d/ sounds, while for Group V the difference was shown with /z/l/ sound (P<0.05). Conclusion. It is recommended to reproduce the rugae area in complete denture because the phonetic quality of complete denture with rugae is superior to the conventional denture.